Exploring Students' Perception of Using Grammarly to Check Grammar in Their Writing - Fitriana, Kesi; Nurazni, Laeli (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
There are many online platforms that can help students to check their grammar. To correct their writing, students usually use online grammar checkers such as Grammarly. This research was conducted to know the English department students’ perspective of Grammarly software as the media to check the grammar in their writing. This research was conducted by using a descriptive qualitative method. The data of this research were taken through a questionnaire. By conducting this research, researchers hope that students can have an idea about Grammarly as one of the online grammar checkers. The result of this research showed that Grammarly gives beneficial for students. Grammarly really helps the students to correct their writing. However, Grammarly still has some drawbacks, such as miscorrection and limited features for the free version, yet students agree that Grammarly helps them a lot.